2014
DOI: 10.1155/2014/723084
|View full text |Cite
|
Sign up to set email alerts
|

Ginseng Is Useful to Enhance Cardiac Contractility in Animals

Abstract: Ginseng has been shown to be effective on cardiac dysfunction. Recent evidence has highlighted the mediation of peroxisome proliferator-activated receptors (PPARs) in cardiac function. Thus, we are interested to investigate the role of PPARδ in ginseng-induced modification of cardiac contractility. The isolated hearts in Langendorff apparatus and hemodynamic analysis in catheterized rats were applied to measure the actions of ginseng ex vivo and in vivo. In normal rats, ginseng enhanced cardiac contractility a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 45 publications
0
9
0
Order By: Relevance
“…Also, rat treated with ginseng (250 or 500 mg/kg) inhibited the myocardial infarction after acute myocardial ischemia reperfusion injury [ 31 ] and isoproterenol-induced cardiac injury in rats [ 32 ]. Moreover, it was mentioned that ginseng (400 mg/kg) may enhance cardiac performance through an increase in the expression of PPAR δ and without altering the heart rate in normal rats [ 33 ]. In the present study, the cardiac performance in diabetic rats was also improved by repeated oral intake of ginseng at 150 mg/kg/day for one week and this used dose is markedly lower than used in previous reports for cardiac diseases [ 7 , 8 , 32 , 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…Also, rat treated with ginseng (250 or 500 mg/kg) inhibited the myocardial infarction after acute myocardial ischemia reperfusion injury [ 31 ] and isoproterenol-induced cardiac injury in rats [ 32 ]. Moreover, it was mentioned that ginseng (400 mg/kg) may enhance cardiac performance through an increase in the expression of PPAR δ and without altering the heart rate in normal rats [ 33 ]. In the present study, the cardiac performance in diabetic rats was also improved by repeated oral intake of ginseng at 150 mg/kg/day for one week and this used dose is markedly lower than used in previous reports for cardiac diseases [ 7 , 8 , 32 , 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…Acute administration of ginseng resulted in depressed cardiac contractile function, as evidenced by reductions in HR and blood pressure that persisted up to 24 h. This acute reduction in cardiac contractility appears to be intrinsic to the myocardium, as spontaneously beating perfused hearts exposed to different concentrations of North American ginseng also demonstrated inhibitory response [ 61 ]. On the contrary, Panax ginseng dramatically increases cardiac contractility in normal rats [ 62 ]. The different in response in contractility may due to the differences in components in ginseng of different origin.…”
Section: Anti-aging Properties Of Ginsengmentioning
confidence: 99%
“…The beating behaviour affected by ginseng could be explained by the molecular mechanisms. In a previous study [33], data of intracellular calcium level and western blotting analysis showed that both the PPAR δ and troponin I phosphorylation were raised by ginseng in neonatal rat cardiomyocyte. Thus, ginseng could enhance cardiac contractility through increased Peroxisome proliferator‐activated receptor (PPAR δ ) protein in the cardiomyocytes.…”
Section: Resultsmentioning
confidence: 99%